Revolution / Stuart Gibbs. - Gibbs, Stuart, 1969- (New York : Simon & Schuster Books for Young Readers, 2021)
With SPYDER defeated, Ben Ripley is looking forward to his life getting back to normal, or as normal as possible when you're a superspy in training. Until someone bombs the CIA conference room next door. To Ben's astonishment, the attacker is none other than Erica Hale, the spy-in-training he respects more than any other. His mission: prove Erica is not a double agent working against the US, locate the fabled colonial-era insurgent group that's blackmailing her, figure out what their devious plot is, and thwart it. But this time, Ben finds himself up against opponents he has never encountered before: his own friends. How can he succeed when he doesn't even know who he can trust?"--from book jacket.
Reading group guide included.
Sequel to: Spy school British invasion.
Sneak peek of Spy school at sea in back of book.
Ages 8-12.
820L
Keywords: United States. -- Central Intelligence Agency -- Juvenile fiction; Spies -- Training of -- Juvenile fiction; Traitors -- Juvenile fiction; Conspiracies -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Spy fiction; Action and adventure fiction